Literature Study Analysis of Sharia Pawnshops in Indonesia - Julfan Saputra; Andri Soemitra (AGHNIYA : Jurnal Ekonomi Islam, 2022)
Pawn is one type of debt-receivable agreement and pawnshop itself is a financial institution, which also encourages the survival of the Sharia Economy. The legitimacy of this pawn practice has existed since the time of the Prophet Muhammad, where the Prophet Muhammad himself carried out this practice. This study aims to analyze Islamic law on the pawn system in sharia pawnshops; the pillars that must be fulfilled if partnering with sharia pawnshops; pawn system in sharia pawnshops; and the factors that influence interest in pawnshops in sharia pawnshops. This type of research is descriptive qualitative research with a literature study approach that comes from books, literature, theses, and library materials related to the purpose of this research. This literature research was conducted during the 2015-2020 period on 38 published fulltext literature.